Pengaruh kualitas pelayanan terhadap kepuasan pelanggan pada new force cafe - Debby Susanti; Pamasang S. Siburian; Asnawati Asnawati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The purpose of this study was to determine the influence of service’s quality which consists of reliability, responsiveness, assurance, empathy and tangibles to customer satisfaction on New Force Cafe in Samarinda. The sample in this study were 98 respondents are from customers who've been, taken by accidental sampling method. Data were analyzed by Multiple Linear Regression Analysis using SPSS version 21. The results of data analysis using SPSS generated regression equation as follows: Y = 0.124 + 0.175 X1 + 0.187 X2 + 0.212 X3 + 0.189 X4 + 0,230 X5 + 0.170. The results of this study show that the reliability, responsiveness, assurance, empathy and tangibles, partially have a positive and significant impact on customer satisfaction.